Provision of standardized all-in-one parenteral nutrition (AIO-PN) for very preterm neonates: Evaluation at room and cold temperatures - Suci Hanifah; Yuli Maulidani; Bambang Hernawan Nugroho; Chynthia Pradiftha Sari (Wolters Kluwer Medknow Publications, 2021)
Introduction: All-in-one parenteral nutrition (AIO-PN) is essential for patients with limited venous access, e.g. premature infants. So far, there are still some conflicting data related to the stability of AIO-PN. The aim of this study is to examine the physical stability and sterility of AIO-PN as it was being stored at room and cold temperature. Materials and Methods: AIO-PN contains dextrose, amino acid, lipid, sodium chloride, magnesium sulfate, potassium chloride, calcium gluconate, and vitamin. Formulation of AIO-PN was prepared based on the guidance of nutrition for 3-day-old preterm baby weighing 1000 g. The formulation of AIO-PN then was stored at room temperature (25.43ºC ± 0.54) and cold temperature (6.2ºC ± 2.04). Results and Discussion: Based on the experiments, all formulas confidently fulfilled the sterile criteria, in which there is no microbial growth in the formula within 7 days. During those days, the droplet size of all formulas was under the range (<500 nm) with a good range of pH. However, during the process of storing under the room temperature, AIO-PN showed the reversible creaming starting on day 2 and the discoloration starting on day 4. Meanwhile, we found that there are no such physical changes in the formula within 7 days under the cold temperature. Conclusion: This research confirmed that AIO-PN that is being stored at room temperature cannot be used starting on day 4, but the formulation storage under the cold temperature is still accepted within 7 days.